The crusade against corruption in Hong Kong in the 1970s: Governor MacLehose as a zealous reformer or reluctant hero?. (July 2013) - Yep, Ray
The creation of the Independent Commission Against Corruption (ICAC) in February 1974 was arguably one of the most important developments in Hong Kong since 1945. Not only did major corruption syndicates disappear from the fabric of public administration in the colony, but the popular acceptance of bribery as a component of social life also faded away. Sir Murray MacLehose, who served as Governor of Hong Kong between 1971 and 1982, was regarded by locals as the maverick behind this miracle. This article argues, however, that the genesis of the ICAC could be better understood as a product of the cumulative efforts of MacLehose and his predecessors. The initiative should also be considered in the political context of the rising tension between London and the local community. In a way, the establishment of the ICAC helped pre-empt London's intervention in this matter. Also, despite a public appearance of unbridled support for the crusade against corruption, MacLehose's resolve was severely tested during the early years of the ICAC, and he did contemplate moderating the operation of the Commission, even before the partial amnesty in 1977.